1994
DOI: 10.1111/j.1432-1033.1994.tb18656.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the myometrial oxytocin receptor into proteoliposomes

Abstract: The requirements for regaining high-affinity binding of the myometrial oxytocin receptor after detergent solubilization were investigated by reconstitution experiments. Large unilamellar liposomes were prepared by reverse-phase evaporation from different mixtures of phospholipids, cholesterol and cholesteryl hemisuccinate. In the presence of the oxytocin receptor solubilized from myometrial membranes from pregnant guinea pig uterus, liposomes were treated with 3-[(3-cholamidopropyl)-dimethylammonio]-2-hydroxy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The oxytocin receptor is the only other GPCR for which it is known that ligand binding also depends on the presence of sterols (36)(37)(38). This receptor belongs to the rhodopsin-like GPCR family, which possesses a ligand-binding pocket in its transmembrane domain.…”
Section: Discussionmentioning
confidence: 99%
“…The oxytocin receptor is the only other GPCR for which it is known that ligand binding also depends on the presence of sterols (36)(37)(38). This receptor belongs to the rhodopsin-like GPCR family, which possesses a ligand-binding pocket in its transmembrane domain.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1990s, Klein and Fahrenholz [80] described reconstitution experiments with the oxytocin receptor (OTR) of guinea pig uterus. These experiments demonstrated that cholesterol is a prerequisite for the highaffinity binding activity (K d in the low nanomolar range) of the myometrial OTR after reconstitution.…”
Section: Review Articlementioning
confidence: 99%
“…Effects of cholesterol on the stability and function of G protein-coupled receptors (GPCRs) have been known for at least two decades (1)(2)(3). However, there is often no clear consensus as to whether the effects of cholesterol on individual protein species arise from a specific GPCR-cholesterol interaction, from the effect of cholesterol on the bulk properties of the lipid bilayer, or from a combination of both (4).…”
Section: Introductionmentioning
confidence: 98%